Sleep deprivation differentially affects subcomponents of cognitive control. Issue 4 (14th January 2019) - Kusztor, Anikó; Raud, Liisa; Juel, Bjørn E; Nilsen, André S; Storm, Johan F; Huster, Rene J
Abstract: Study Objectives: Although sleep deprivation has long been known to negatively affect cognitive performance, the exact mechanisms through which it acts and what cognitive domains are affected most is still disputed. The current study provides a theory-driven approach to examine and explain the detrimental effects of sleep loss with a focus on attention and cognitive control. Methods: Twenty-four participants (12 females; age: 24 ± 3 years) completed the experiment that involved laboratory-controlled over-night sleep deprivation and two control conditions, namely, a normally rested night at home and a night of sleep in the laboratory. Using a stop signal task in combination with electroencephalographic recordings, we dissociated different processes contributing to task performance such as sustained attention, automatic or bottom-up processing, and strategic or top-down control. At the behavioral level, we extracted reaction times, response accuracy, and markers of behavioral adjustments (post-error and post-stop slowing), whereas at the neural level event-related potentials (ERP) found in context of response inhibition (N2/P3) and error monitoring (ERN/Pe ) were obtained. Results: It was found that 24 hr of sleep deprivation resulted in declined sustained attention and reduced P300 and Pe amplitudes, demonstrating a gradual breakdown of top-down control. In contrast, N200 and ERN as well as the stop-signal reaction time showed higher resilience to sleep loss signifying the role of automatic processing. Conclusions: These results support the notion that sleep deprivation is more detrimental to cognitive functions that are relatively more dependent on mental effort and/or cognitive capacity, as opposed to more automatic control processes.